Avaliação dos efeitos toxicológicos dos espermatozoides de jundiá (rhamdia quelen) em diferentes concentrações de HgCl2 - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The Jundiá (Rhamdia quelen) is a fish that stands out in the south of Brazil, can be found from the center of Argentina to the south of Mexico, stands out due to easy adaptation and good reproductive performance, sexual maturity is reached in the first year of life presenting two reproductive peaks a year, one in summer and one in the spring. Studies related to gamete behavior and its interaction with the environment are still incipient, the gametes are released into the environment where fertilization occurs and this time they are exposed to various contaminants in the water, such as heavy metals, such as chloride mercury (HgCl2) which is capable of causing damage to any tissue in which contact. In view of this, the study aimed to evaluate the pathologies caused by morphological damage caused by the activation of sperm with solutions of different concentrations of HgCl2. For the study, semen collection was made, which were used 7 male animals of reproductive age (489.42 ± 137g and 36.78 ± 3,13cm). Semen was collected by abdominal compression, activated in NaCl HgCl2 free 50 mM solution to the control group, and 50 mM NaCl solutions with 0.0001; 0.0002; 0.002 and 0.02 mg / L of HgCl2. Were evaluated motility, vigor and motility time as subjective parameters, integrity and membrane fluidity, mitochondrial functionality, reactive oxygen species and DNA fragmentation and cell toxicity parameters and sperm morphology and cell morphology parameter. The results indicate that in relation to motility parameters, vigor and motility time, there were differences when compared to the control group even in the lowest concentration evaluated (0,0001mg / L). However, cell damage were observed only from the dose 0,0002mg / L, where they membrane integrity and fluidity thereof. In the morphological parameter, there was difference between the abnormal cell ratio between the control group and all concentrations evaluated in the treated groups. These results indicate that mercuric chloride can cause damage to sperm R. quelen at all concentrations tested.
Assessment of toxicological effects of sperm jundiá (quelen Rhamdia) in different concentrations of HgCl2
Keywords: Peixes; Reprodução animal; Jundiá; Metais Pesados; Toxicologia; Piscicultura; Rhamdia quelen